2012
DOI: 10.1002/j.2168-0159.2012.tb05927.x
|View full text |Cite
|
Sign up to set email alerts
|

65.1: Effective Spatial Resolution of Temporally and Spatially Interlaced Stereo 3D Televisions

Abstract: We measured the effective spatial resolution of temporally and spatially interlacing of stereo three-dimensional (S3D) televisions at three different viewing distances: 1.5, 3 and 6 times picture height. Temporally interlacing S3D television has significantly better effective resolution at viewing distances of 1.5 and 3 times picture height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Kim and Banks [2] measured effective spatial resolution with spatial and temporal interlacing at different viewing distances. They found that viewers' ability to discern fine detail was reduced with spatial interlacing provided that the viewing distance was not too great.…”
Section: Experiments 3: Spatial Resolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kim and Banks [2] measured effective spatial resolution with spatial and temporal interlacing at different viewing distances. They found that viewers' ability to discern fine detail was reduced with spatial interlacing provided that the viewing distance was not too great.…”
Section: Experiments 3: Spatial Resolutionmentioning
confidence: 99%
“…At long distances, where pixels are too small to be resolved by the visual system, resolution becomes "eye limited" [2]. The size and arrangement of pixels will therefore not matter to the viewer's ability to see fine detail.…”
Section: Experiments 3: Spatial Resolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…The viewer wears passive glasses that contain filters with opposite polarization states such that one eye sees the images presented on odd pixel rows while the other eye sees the images presented on even rows [1,2]. By sending information simultaneously to the two eyes, spatial interlacing is not as prone to temporal artifacts as other techniques [3].…”
Section: Introductionmentioning
confidence: 99%